Limits to exercise performance in the heat - Hargreaves, M.; Febbraio, M. (International Journal of Sports Medicine, 1998)
Exercise in the heat results in major alterations in circulatory, thermoregulatory and metabolic function. Hyperthermia appears to be the critical determinant of exercise performance in the heat. Thus, strategies that minimise the rise in core temperature during exercise in the heat are likely to contribute to enhanced performance. These include acclimatisation to heat, adequate hydration prior to exercise and ingestion of fluids during exercise, and pre-exercise cooling.